The Concept of Profit In Syirkah Al-‘Inān Islamic Economic Perspective: Study at People's Banks Ipoh, Perak Malaysia - Athailah Junaidy; Muhammad Ikbal; Zulhamdi Zulhamdi (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2023)
This research is about studying the concept of